2004
DOI: 10.1002/ajh.20083
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of deletional α‐thalassemia in β‐thalassemia trait: Implications for genetic counseling

Abstract: Thalassemias are a group of genetic hemolytic disorders with varying phenotypes. In this study, the frequency of a globin gene deletions was studied in the b-thalassemia trait, the mildest form of the disorder. Eleven out of 33 (33%) individuals were positive for a -3.7 kb deletions. None of the subjects was positive for the Southeast Asian deletion. Such a high frequency for a deletions has not been reported earlier in thalassemia minor. Hematological parameters are compared, and implications of this finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The frequency of -á 3.7 deletion in thalassemia trait is 10.3%. A recent study has shown a high frequency of carrier status in â-thalassemia trait (Panigrahi et al 2004) and its implication in prenatal diagnosis. The coinheritance of á-gene deletion and triplication with â-thalassemia is important as a factor modifying the phenotypic expression.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of -á 3.7 deletion in thalassemia trait is 10.3%. A recent study has shown a high frequency of carrier status in â-thalassemia trait (Panigrahi et al 2004) and its implication in prenatal diagnosis. The coinheritance of á-gene deletion and triplication with â-thalassemia is important as a factor modifying the phenotypic expression.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Most alpha thalassemia cases in India have been reported among tribal populations 8 , 9 with βTT and other hemoglobinopathies but its co-existence with IDA has never been studied. 7 , 10 13 Iron deficiency is highly prevalent in India and with the reportedly high frequency of α thalassemia the likelihood of the two conditions coexisting can be expected to be high. The Discrimination between microcytosis due to the two conditions is not only clinically significant but is often difficult even more so when they coexist.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of double heterozygosity for different types of thalassemias is high in populations where thalassemia is frequent and the most common form of this situation is the combining heterozygosity for β thalassemia and α thalassemia (11). As is known, α thalassemia carried by β thalassemia heterozygotes is deletional type (12) and red cell parameters in β thalassemia heterozygotes combining deletional α thalassemia are found to be similar to those in pure β thalassemia (13), as also observed in the mother. Instead, these two clinical conditions have come together in the index case, and this coexistence led to the clinical symptoms.…”
Section: Discussionmentioning
confidence: 58%